Typological thinking: Then and now. Issue 3 (26th March 2018) - Witteveen, Joeri
Abstract: A popular narrative about the history of modern biology has it that Ernst Mayr introduced the distinction between "typological thinking" and "population thinking" to mark a contrast between a metaphysically problematic and a promising foundation for (evolutionary) biology, respectively. This narrative sometimes continues with the observation that, since the late‐20th century, typological concepts have been making a comeback in biology, primarily in the context of evolutionary developmental biology. It is hard to square this narrative with the historical and philosophical literature on the typology/population distinction from the last decade or so. The conclusion that emerges from this literature is that the very distinction between typological thinking and population thinking is a piece of mere rhetoric that was concocted and rehearsed for purely strategic, programmatic reasons. If this is right, it becomes hard to make sense of recent criticisms (and sometimes: espousals) of the purportedly typological underpinnings of certain contemporary research programs. In this article, I offer a way out of this apparent conflict. I show that we can make historical and philosophical sense of the continued accusations of typological thinking by looking beyond Mayr, to his contemporary and colleague George Gaylord Simpson. I show that before Mayr discussed the typology/population distinction as an issue in scientific metaphysics, Simpson introduced it to mark several contrasts in methodology and scientific practice. I argue that Simpson's insightful discussion offers useful resources for classifying and assessing contemporary attributions of typological thinking.